Study of risk factors associated with malnutrition in children admitted to a sub-district hospital - Barot, Nimesh; Teckchandani, Rajeshkumar; Patel, Uchit; Parmar, Aditya (International Journal of Contemporary Pediatrics, 2025)
Background: Malnutrition remains a significant public health concern among children, particularly in resource-limited settings. Identifying the underlying risk factors is essential for targeted interventions. This study aims to assess the risk factors associated with malnutrition in children admitted to a sub-district hospital. Methods: A cross-sectional study was conducted among children aged 6 months to 5 years admitted to the paediatric ward of a sub-district hospital over a 6-month period. Nutritional status was assessed using World Health Organization (WHO) growth standards. Data on socio-demographic variables, feeding practices, maternal education, socioeconomic status, birth weight, and presence of infections were collected through structured interviews with caregivers and review of medical records. Statistical analysis was performed to identify significant associations between these factors and malnutrition. Results: Out of 100 children assessed, 15% were severely malnourished, 32% were moderately malnourished, and 53% had normal nutritional status based on mid-upper arm circumference (MUAC). Low birth weight, lack of exclusive breastfeeding, low maternal education, and poor socioeconomic status were all significantly associated with higher rates of malnutrition. Children with low birth weight were 3.7 times, non-exclusively breastfed children 5.6 times, and those from low socioeconomic backgrounds 4.6 times more likely to be malnourished. Anaemia showed no significant association with malnutrition, possibly due to the small sample size. Overall, the findings highlight the multifactorial nature of childhood malnutrition, influenced by perinatal, maternal, and socioeconomic factors. Conclusion: The present study revealed that a considerable proportion of children suffer from varying degrees of malnutrition. Low birth weight, non-exclusive breastfeeding, low maternal education, and poor socioeconomic conditions were found to be significant risk factors. Anaemia, although prevalent, did not show a significant association. These findings emphasize the need for early preventive strategies focusing on maternal and child health, breastfeeding promotion, and social empowerment to combat childhood malnutrition effectively.